2022
DOI: 10.3390/jcm11185369
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis Indices Predict the Severity of SARS-CoV-2 Infection

Abstract: Discovering novel risk and prognostic factors for COVID-19 may help not only in reducing severity and mortality but also in creating targeted therapies considering patients’ individual features. Liver fibrosis is considered a complication in Non-alcoholic Fatty Liver Disease (NAFLD), it is a feature of steatohepatitis (NASH), and it has already been related to an increased risk for a wide range of diseases. Here, we aimed to define if any parameter assessing metabolic status has predictive power in identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…This is also consistent with prior smaller studies that have been single‐center or single health system in design 10 . Higher scores on traditional non‐invasive liver scoring systems, such as APRI, FIB‐4, NFS, and MELD have also been shown to carry worse prognosis in patients infected with COVID‐19 in both patients with cirrhosis and independent of a diagnosis of liver disease 22–25 with a MELD score ≥ 18.5 predicting in‐hospital mortality with a 99% sensitivity and 100% specificity 26 . However, given the absence of laboratory data in the NIS, we were unable to validate these observations from prior studies.…”
Section: Discussionsupporting
confidence: 81%
“…This is also consistent with prior smaller studies that have been single‐center or single health system in design 10 . Higher scores on traditional non‐invasive liver scoring systems, such as APRI, FIB‐4, NFS, and MELD have also been shown to carry worse prognosis in patients infected with COVID‐19 in both patients with cirrhosis and independent of a diagnosis of liver disease 22–25 with a MELD score ≥ 18.5 predicting in‐hospital mortality with a 99% sensitivity and 100% specificity 26 . However, given the absence of laboratory data in the NIS, we were unable to validate these observations from prior studies.…”
Section: Discussionsupporting
confidence: 81%
“…These increases in liver fibrosis scores among SARS‐CoV‐2‐infected patients may reflect liver fibrosis. However, previous studies have reported that liver fibrosis scores were lower at discharge compared with the time of admission in patients with COVID‐19, 23,25 a finding corroborated by the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous several studies reported an association between COVID‐19 severity and liver fibrosis scores. However, the mechanisms underlying the association between liver fibrosis scores and COVID‐19 severity have yet to be fully elucidated 3,20–23 . A previous study reported that serum SARS‐CoV‐2 RNA levels were associated with COVID‐19 severity 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations